Neuronal and microglial regulators of cortical wiring: usual and novel guideposts - Squarzoni, Paola; Thion, Morgane S.; Garel, Sonia (Frontiers in Neuroscience, 2015)
Neocortex functioning relies on the formation of complex networks that begin to be assembled during embryogenesis by highly stereotyped processes of cell migration and axonal navigation. The guidance of cells and axons is driven by extracellular cues, released along by final targets or intermediate targets located along specific pathways. In particular, guidepost cells, originally described in the grasshopper, are considered discrete, specialized cell populations located at crucial decision points along axonal trajectories that regulate tract formation. These cells are usually early-born, transient and act at short-range or via cell-cell contact. The vast majority of guidepost cells initially identified were glial cells, which play a role in the formation of important axonal tracts in the forebrain, such as the corpus callosum, anterior, and post-optic commissures as well as optic chiasm. In the last decades, tangential migrating neurons have also been found to participate in the guidance of principal axonal tracts in the forebrain. This is the case for several examples such as guideposts for the lateral olfactory tract (LOT), corridor cells, which open an internal path for thalamo-cortical axons and Cajal-Retzius cells that have been involved in the formation of the entorhino-hippocampal connections. More recently, microglia, the resident macrophages of the brain, were specifically observed at the crossroads of important neuronal migratory routes and axonal tract pathways during forebrain development. We furthermore found that microglia participate to the shaping of prenatal forebrain circuits, thereby opening novel perspectives on forebrain development and wiring. Here we will review the last findings on already known guidepost cell populations and will discuss the role of microglia as a potentially new class of atypical guidepost cells.